2021
DOI: 10.1002/eap.2399
|View full text |Cite
|
Sign up to set email alerts
|

Browsing wildlife and heavy grazing indirectly facilitate sapling recruitment in an East African savanna

Abstract: Management of tree cover, either to curb bush encroachment or to mitigate losses of woody cover to over‐browsing, is a major concern in savanna ecosystems. Once established, trees are often “trapped” as saplings, since interactions among disturbance, plant competition, and precipitation delay sapling recruitment into adult size classes. Saplings can be directly suppressed by wildlife browsing and competition from adjacent plants, and indirectly facilitated by grazers, such as cattle, which feed on neighboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 110 publications
(317 reference statements)
1
7
0
Order By: Relevance
“…In our study, we focussed on a subset of these factors and found that when perennial grass cover decreased significantly or recovered too slowly, shrubs used their competitive advantage in the acquisition of water from deep soil layers and shrub seedlings established on the available space hence limiting the regrowth of grasses. These results are also in line with previous findings showing that grass removal increased sapling growth and woody plant cover (LaMalfa et al, 2021). Additionally, our model showed the stabilising effect of reduced herbivory pressure on grasses initiated by the introduction of browsing herbivores.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we focussed on a subset of these factors and found that when perennial grass cover decreased significantly or recovered too slowly, shrubs used their competitive advantage in the acquisition of water from deep soil layers and shrub seedlings established on the available space hence limiting the regrowth of grasses. These results are also in line with previous findings showing that grass removal increased sapling growth and woody plant cover (LaMalfa et al, 2021). Additionally, our model showed the stabilising effect of reduced herbivory pressure on grasses initiated by the introduction of browsing herbivores.…”
Section: Discussionsupporting
confidence: 93%
“…This effect may be particularly strong at Ol Pejeta Conservancy due to relatively high densities of elephants, black rhinoceroses, and other ungulates, which frequently browse saplings and small trees (Wahungu et al, 2009). Recent work at Mpala Research Centre, a nearby, uninvaded study system with lower elephant densities and no rhinos, found muted effects of herbivory on saplings (LaMalfa et al, 2021). Additionally, and in previous studies on A. drepanolobium , LMH forced the reallocation of energy from reproduction to defensive investment (spines), further reducing λ by limiting reproduction (Goheen et al, 2007; Maclean et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to increase survival of small trees and allow them to grow to larger, less vulnerable sizes could be used to bolster population growth rates and stabilize populations. A recent study showed that A. drepanolobium saplings grow rapidly in years of heavy rainfall when protected from browsing pressure (LaMalfa et al, 2021). Targeted fencing of small trees in high rainfall years or with irrigation could help to buffer acacia populations against increasing numbers of mega-browsers.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated here that if grazers replace browsers and reduce grass competition in combination with the loss of fire (a scenario that is occurring due to intensive cattle grazing across many African savanna systems [Hempson et al, 2015; Probert et al, 2019; Veldhuis, Ritchie et al, 2019; Venter et al, 2018]), then seedling establishment may experience a ~7.5‐fold increase. Riginos (2009) found that the negative competitive effects of grasses on tree growth persists across all demographic stages and LaMalfa et al (2021) found that if high grazing pressure persists, even in the presence of browsing, then established saplings have a higher likelihood of recruiting to the next demographic stage. Thus, our results provide strong experimental evidence in this system to support the theory that historic tree cover change in the Serengeti was driven by cascading impacts during the collapse and subsequent recovery of the wildebeest population (Holdo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results provide strong experimental evidence in this system to support the theory that historic tree cover change in the Serengeti was driven by cascading impacts during the collapse and subsequent recovery of the wildebeest population (Holdo et al, 2009). More broadly, our findings align with previous work showing that savanna tree:grass ratios are sensitive to the direct and indirect effects of grazers and browsers with changes to either herbivore guild capable of driving sudden shifts in system structure and function (Goheen et al, 2010; LaMalfa et al, 2019, 2021; O'Connor et al, 2014; Van Langevelde et al, 2003).…”
Section: Discussionmentioning
confidence: 99%